Comparison of the Effect of Trabeculectomy with Mitomycin C on Macular Thickness in Primary Open-Angle Glaucoma and Pseudoexfoliative Glaucoma - Ufuk Elgin; Emine Şen; Hakan Tırhış (Türk Oftalmoloji Dergisi, 2012)
Pur po se: To compare the effect of trabeculectomy with mitomycin C (mit C) on central macular thickness (CMT) in primary openangle glaucoma (POAG) and pseudoexfoliative glaucoma (PXG). Ma te ri al and Met hod: 13 eyes with PXG and 11 eyes with POAG, which had undergone trabeculectomy with mit C, were included to our prospective study. Cases with histories of any systemic vascular diseases and previous ocular surgeries were not included. The CMT was measured by spectral-domain optical coherence tomography (SD-OCT) before the surgery and at the first postoperative week and month. Pre-and postoperative values of both groups and the differences between the two groups were compared statistically by Mann-Whitney U and Wilcoxon signed rank tests. Re sults: The means of CMT at the first postoperative week and month were statistically significantly higher than the preoperative values in both POAG and PXG groups (POAG: 1st week p=0.0090, 1st month p=0.0086; PXG: 1st week p=0.0023, 1st month p=0.0050). However, no statistically significant differences were found between the changes of preoperative and postoperative mean CMT values between the two groups (1st week p=0.4326, 1st month p=0.5028). Dis cus si on: In spite of the increases in CMT at the 1st week and month of trabeculectomy with mit C in POAG and PXG, no significant differences were detected between the changes of CMT between the two groups. Based on the fact that more inflammation and higher decrease in intraocular pressure might be seen in PXG than POAG postoperatively, further investigations with great number of cases are planned. (Turk J Ophthalmol 2012; 42: 1-4)